The impact of the 2013 rule changes on gripping configuration in high-level judo athletes - Nemanja Stanković; Nikola Milošević; Mladen Živković (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2019)
Purpose: International Judo Federation introduced a set of new rules in a short time period (2009 − 2013). The aim of this research is to determine how the rule modification influences the gripping configurations used by elite male judo athletes. Methods: The sample contained 280 combats from the 2011 and 2014 World Championships. All the effective and ineffective throw attempts with related gripping configurations were registered. The Chi-square test was used to determine the difference between frequencies, along with Z-test for calculating the partial difference. Results: A total of 1707 actions and gripping configurations were registered. The Chi-square test showed that there is a significant difference in the usage of gripping configurations between the two championships (χ2=32,8; sig<0,001). The Z-test showed a significant increase in the usage of kenka-yotsu and ai-yotsu, and a significant decrease in the usage of central grip, cross grip and situations where only tori has established a grip. The difference in the usage of the same side grip was not detected. Conclusion: The recommendation for coaches is to reduce the use of all other gripping configurations except kenka-yotsu and ai-yotsu when practicing techniques, especially unorthodox gripping like the cross grip and the same side grip.